Gut microbiota decreased inflammation induced by chronic unpredictable mild stress through affecting NLRP3 inflammasome - Huang, Li; Ma, Zewei; Ze, Xiaolei; Zhao, Xinrui; Zhang, Meilin; Lv, Xia; Zheng, Yunqin; Liu, Huan (Frontiers in Cellular and Infection Microbiology, 2023)
Dysbiosis of the gut microbiota is associated with the development of depression, but the underlying mechanism remains unclear. The aim of this study was to determine the relationship between microbiota and NLRP3 inflammasome induced by chronic unpredictable mild stress (CUMS). Fecal transplantation (FMT) experiment was conducted to elucidate the potential mechanism. Levels of NLRP3 inflammasome, microbiota, inflammatory factors and tight junction proteins were measured. CUMS stimulation significantly increased the levels of NLRP3, Caspase-1 and ASC in brain and colon(p<0.05), decreased the levels of tight junction proteins Occludin and ZO-1 (p<0.05). Interestingly, increased NLRP3 inflammasome and inflammatory cytokines and decreased tight junction proteins were found in antibiotic-treated (Abx) rats received CUMS rat fecal microbiota transplantation. Furthermore, fecal microbiota transplantation altered the microbiota in Abx rats, which partially overlapped with that of the donor rats. Importantly, probiotic administration amended the alteration of microbiota induced by CUMS treatment, then reduced the levels of NLRP3 inflammasome and inflammatory factors. In conclusion, these findings suggested that depression-like behaviors induced by CUMS stimulation were related to altered gut microbiota, broke the intestinal barrier, promoted the expression of NLRP3 inflammasome and elevated inflammation. Therefore, improving the composition of microbiota via probiotic can attenuate inflammation by amending the microbiota and suppressing the activation of NLRP3 inflammasome, which is considered as a novel therapeutic strategy for depression.